1987
DOI: 10.1177/00220345870660080501
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-culture Chemostat System to Predict the Effect of Anti-microbial Agents on the Oral Flora: Preliminary Studies using Chlorhexidine

Abstract: A mixed-culture chemostat system, composed of nine bacterial species representative of plaque in health and disease, has been assessed as an improved laboratory method of evaluating the likely in vivo effects of antimicrobial agents used in dentistry. The advantages of the system include reproducibility, the long-term stable cultivation of bacteria under controllable conditions, and repeated sampling, for bacteriological and biochemical studies, without disrupting the stability of the community. The effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 32 publications
3
36
0
Order By: Relevance
“…Addition of CHX caused the loss of A. naeslundii from in vitro CDFF plaques, while Porphyromonas gingivalis was markedly inhibited (19). Similarly, defined community chemostat studies confirmed the non- (29), suggesting that hierarchies of susceptibility in pure culture can be extrapolated to community effects. In a previous study, large variations in the composition of microcosm plaques in replicate fermenters were demonstrated using the same pooled saliva as inocula (28).…”
Section: Discussionmentioning
confidence: 70%
“…Addition of CHX caused the loss of A. naeslundii from in vitro CDFF plaques, while Porphyromonas gingivalis was markedly inhibited (19). Similarly, defined community chemostat studies confirmed the non- (29), suggesting that hierarchies of susceptibility in pure culture can be extrapolated to community effects. In a previous study, large variations in the composition of microcosm plaques in replicate fermenters were demonstrated using the same pooled saliva as inocula (28).…”
Section: Discussionmentioning
confidence: 70%
“…Despite reduction of mutans streptococci levels, oral streptococci were not total, suggesting that the site and function of mutans streptococci in oral ecosystem may be occupied by other bacteria, probably some strain of streptococci not reduced by this treatment. This hypothesis is supported by the fact that some oral streptococci strains show variable susceptibility to chlorhexidine and fluoride (17,19,21). Concerning oral lactobacilli, levels were not reduced by fluoride and chlorhexidine probably because these microorganisms were hidden in habitats not affected by these products as observed among irradiated patients (12).…”
Section: Oral Streptococcimentioning
confidence: 84%
“…action of chlorhexidine (19,20) followed its bacteriostatic action that in association with fluoride would inhibit bacterial metabolism in different sites. Bacterial recolonization is observed after some days (26,29) or months based on adopted treatment, infection levels, sucrose ingestion or dental restorations.…”
Section: Oral Streptococcimentioning
confidence: 99%
See 1 more Smart Citation
“…chlorhexidine, Triclosan) can lead to unexpected favourably selective antimicrobial effects. Target species such as S. mutans and Gram-negative anaerobes remain sensitive while many species associated with dental health are relatively unaffected by these short contact times with inhibitors (Bradshaw et al, 1993;Kinniment et al, 1996b;McDermid et al, 1987). In addition, these agents at sub-MIC levels reduce metabolism by inhibiting glycolysis, sugar transport and proteases, which again will help to stabilize microbial communities and maintain homeostasis (Cummins, 1991;Marsh et al, 1983b).…”
Section: Inhibition Of Acid Productionmentioning
confidence: 99%